2020
DOI: 10.7717/peerj.10367
|View full text |Cite
|
Sign up to set email alerts
|

Third molar agenesis in modern humans with and without agenesis of other teeth

Abstract: Background The number of teeth in the human dentition is of interest both from developmental and evolutionary aspects. The present case-control study focused on the formation of third molars in modern humans aiming to shed more light on the most variable tooth class in the dentition. Materials and Methods For this reason, we investigated third molar formation in a sample of 303 individuals with agenesis of teeth other than third molars (agenesis group) and compared it to a sex and age matched control group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
3
27
0
4
Order By: Relevance
“…Third molars were excluded from this analysis, which are often ignored in oligodontia studies because of the high frequency of their absence (~20%) in the general population, although third molar absence is significantly higher in persons missing teeth other than third molars. 14 Furthermore, ten families with oligodontia were recruited and characterized with clinical examinations and the causative mutation determined by genotype analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Third molars were excluded from this analysis, which are often ignored in oligodontia studies because of the high frequency of their absence (~20%) in the general population, although third molar absence is significantly higher in persons missing teeth other than third molars. 14 Furthermore, ten families with oligodontia were recruited and characterized with clinical examinations and the causative mutation determined by genotype analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in cases where all other permanent teeth are present, an agenesis of the third molars is largely viewed as a normal phenotype. Nevertheless, previous studies have shown that there is a strong association between missing third molars and agenesis of other teeth, with the latter increasing the chance of third molar agenesis by approximately 40% [4][5][6]. This raises the question, whether the presence of third molars is controlled by the same genetic mechanisms as other permanent teeth, or their formation follows a separate developmental pattern.…”
Section: Introductionmentioning
confidence: 98%
“…Las dimensiones faciales sufrirán notables disminuciones en algunos de sus segmentos, estas modificaciones se hacen evidentes en la Anchura Bicigomática, Altura Nasion-Prostion, Anchura y Altura Nasal, Anchura y Altura Orbital, Anchura Interorbitaria, Achura Biorbital, Anchura Bimaxilar y Anchura Maxilo-Alveolar. Es conveniente mencionar que la configuración facial pronosticada podría repercutir sobre el número total de piezas dentarias, debido a que el mecanismo biológico ajusta uniformemente el tamaño facial y el número de dientes (Oeschger et al, 2020;Scheiwiller et al, 2020).…”
Section: Discussionunclassified